Abnormal Nipple Discharge - Yamamoto, Daigo; Chiba, Tsukuru; Ishizuka, Mariko; Sueoka, Noriko; Yoshikawa, Katsuhiro; Miyata, Mami; Ueda, Aiko; Tsubota, Yu (Gan to kagaku ryoho, 2019)
Breast carcinoma and precancer are thought to start in the lining of the milk duct or lobule. Ductography and fiberoptic ductoscopy have beenadvocated as the mainprocedures inpatien ts with nipple discharge. We investigated the usefulness of microdochectomy(MD)by using indocyanine green(ICG)fluorescence imaging. ICG and indigo carmine were injected into the mammary duct. A periareolar incision was made, and a fluorescence image of the demarcated mammary duct segment was obtained. MD using indocyanine green fluorescence imaging is a useful procedure in guiding subsequent breast surgery in the treatment of nipple discharge.